1991
DOI: 10.2105/ajph.81.7.891
|View full text |Cite
|
Sign up to set email alerts
|

Sustained effects of an educational program to reduce sales of cigarettes to minors.

Abstract: We report 1-year follow-up data from a sample of stores participating in a 6-month community-wide educational effort to reduce cigarette sales to minors in Santa Clara County, California. The proportion of over-the-counter sales to minors at the 1-year follow-up illustrated that although statistically significant reductions were maintained 6 months after the intervention ended, recidivism occurred. Suggestions for achieving long-term reductions in sales to minors are offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 13 publications
0
36
1
Order By: Relevance
“…The first of the studies evaluating this approach took place in Santa Clara County, California. Following an intensive six-month effort, purchase success was reduced from 74% to 39%, but six months after the intervention ended, purchase success rebounded to 59% (3,4). A study conducted in San Diego County with a more intensive intervention, including newspaper reports of purchase outcomes, showed a significant reduction in purchase success that was sustained over six months following the end of intervention (80,131).…”
Section: Evidence For Effectiveness Of Youth Access Policiesmentioning
confidence: 99%
“…The first of the studies evaluating this approach took place in Santa Clara County, California. Following an intensive six-month effort, purchase success was reduced from 74% to 39%, but six months after the intervention ended, purchase success rebounded to 59% (3,4). A study conducted in San Diego County with a more intensive intervention, including newspaper reports of purchase outcomes, showed a significant reduction in purchase success that was sustained over six months following the end of intervention (80,131).…”
Section: Evidence For Effectiveness Of Youth Access Policiesmentioning
confidence: 99%
“…Another study found that any short-term gain as a result of intervention is unlikely to be sustained. 16 These intervention studies aiming to reduce the sale of cigarettes to minors, however, have methodological weaknesses that limit the interpretation of their findings. These include the lack of a control g r o u~,~~~~, '~ lack of a pre test,I7 and inadequate ~a m p l i n g .…”
mentioning
confidence: 99%
“…Few states emulated their successful peers, opting instead to rely upon educational approaches that had previously failed. 20 Many states took in far more revenue from underage sales than they spent on enforcement. 21 States that enacted laws that protected lawbreaking merchants from prosecution often adopted Although merchant education may be important to achieving very low violation rates, it appears to be inadequate as a sole strategy.…”
Section: Enforcementmentioning
confidence: 99%
“…This was ill advised, as previous attempts to maintain low violation rates without issuing penalties had failed. 20 It could be argued that existing data were limited and states should be free to experiment with alternatives. However, in the end, no state achieved the 20% goal without punishing lawbreakers.…”
Section: Lowering the Goal Posts By Renegotiating Targetsmentioning
confidence: 99%